Re: Quitting smoking and gaining weight: the odd couple - Aveyard, P; Farley, A; Lycett, D; Aubin, H (BMJ Publishing Group, 2012)
We are grateful to Fernandez and Chapman for the interest in our work. We concur completely that the risk of weight gain should not deter people from quitting smoking. The reduction in risk from cessation far outweighs the risks from weight gain. However, we are concerned that the phrasing and some of the messages in the editorial may give the wrong impression. The authors suggest that the results may not apply to most smokers, seem to imply that the weight gain is temporary, and that the weight gain may not matter to health.